Institutional amnesia and public policy. Issue 10 (3rd October 2019) - Stark, Alastair; Head, Brian
ABSTRACT: Institutional amnesia continues to be ignored by policy scholars despite the fact that it can undermine the effectiveness of public policy in various ways. In calling on policy scholars to start taking amnesia seriously as a research concern, this article provides data and analytical tools to help develop that agenda. The data are drawn from an international comparison of policy learning and amnesia in four Westminster systems (Australia, Canada, New Zealand, UK), which highlights how public-sector leaders widely regard amnesia as a serious matter of concern. Analytical tools are presented in the form of a working definition of amnesia that can operationalize research; a series of hypotheses about how amnesia can act as an independent variable in relation to other policy concerns; and a variety of research-based pathways through which policy practitioners might seek to address the risk of memory-loss.